Cartera Vencida De Las Cuentas Por Cobrar Del Comercial DISMERO S.A. - Otacoma Taipe, Diana Elizabeth (2018)
The companies that are dedicated to the activity of buying and selling products of first need to the largest customers, and tend to appreciate two measures of collection both as in cash and on credit. Credit in current times is considered a great relevance for this class of entities, is a technique to captivate the market and thus obtain greater profitability. DISMERO S.A is a company that deals with the wholesale of products of mass consumption, trying thus to supply the basic needs of the consumer, represents the place where this case study was conducted with the subject PORTFOLIO EXPIRED FROM THE ACCOUNTS COLLECTED FROM THE COMMERCIAL DISMERO S.A, and through the information obtained it is possible to identify the processes made from the moment in which the customer requires the purchase on credit, and the phases applied by the company to raise the portfolio. The objective of this research is to recognize the processes and policies in the area of credit and collections for the recovery of overdue portfolios in the company where the buyers, are part of the delinquent customers due to the bad process and evaluation of the credit amounts to be granted to each of them. The proposal is attributed to a mechanism that enables the effective management of accounts receivable from the company guaranteeing recovery, and thus considering the liquidity and sustainable values ​​of the company's operations for this reason is considered of great relevance. This present work is framed in the research subline "Management of accounting information" and was carried out verifying what is stipulated in the lines of investigation of the school of accounting, auditing and finance.